The Crust and Upper Mantle Structure of Central and West Antarctica From Bayesian Inversion of Rayleigh Wave and Receiver Functions. Issue 9 (22nd September 2018) - Shen, Weisen; Wiens, Douglas A.; Anandakrishnan, Sridhar; Aster, Richard C.; Gerstoft, Peter; Bromirski, Peter D.; Hansen, Samantha E.; Dalziel, Ian W. D.; Heeszel, David S.; Huerta, Audrey D.; Nyblade, Andrew A.; Stephen, Ralph; et al.
Abstract: We construct a new seismic model for central and West Antarctica by jointly inverting Rayleigh wave phase and group velocities along with P wave receiver functions. Ambient noise tomography exploiting data from more than 200 seismic stations deployed over the past 18 years is used to construct Rayleigh wave phase and group velocity dispersion maps. Comparison between the ambient noise phase velocity maps with those constructed using teleseismic earthquakes confirms the accuracy of both results. These maps, together with P receiver function waveforms, are used to construct a new 3‐D shear velocity (Vs) model for the crust and uppermost mantle using a Bayesian Monte Carlo algorithm. The new 3‐D seismic model shows the dichotomy of the tectonically active West Antarctica (WANT) and the stable and ancient East Antarctica (EANT). In WANT, the model exhibits a slow uppermost mantle along the Transantarctic Mountains (TAMs) front, interpreted as the thermal effect from Cenozoic rifting. Beneath the southern TAMs, the slow uppermost mantle extends horizontally beneath the traditionally recognized EANT, hypothesized to be associated with lithospheric delamination. Thin crust and lithosphere observed along the Amundsen Sea coast and extending into the interior suggest involvement of these areas in Cenozoic rifting. EANT, with its relatively thick and cold crust and lithosphere marked by high Vs, displays a slower Vs anomaly beneath the Gamburtsev Subglacial Mountains in the uppermost mantle, which we hypothesize may be the signature of a compositionally anomalous body, perhaps remnant from a continental collision. Key Points: We present a new 3‐D crustal and uppermost mantle model for central and West Antarctica based on 15 years of seismic data Surface waves from ambient noise and earthquakes and receiver functions are combined to improve the resolution New features such as an uppermost mantle anomaly beneath the Gamburtsev Mountains are discussed